Implementation of Public Service Policy at the White Water Crossing Technical Unit of the Bengkalis Regency Transportation Service - Salamun, Salamun (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The aim of this research is to determine the implementation of public service principles in the technical implementation unit of the Air Putih crossing of the Bengkalis Regency Transportation Service. The research method used is a qualitative approach through descriptive surveys and data reduction techniques. The data source is from the informant as the head of the UPT as. Data collection techniques include in-depth interviews, field observations to observe events in the research field, documentation in the form of results from other people in the form of archives and other documentation. The conclusion of this research states that the implementation of public services in the White Water Crossing Technical Implementation Unit of the Bengkalis Regency Transportation Service is quite implemented, but still needs to be improved and improved services based on indicators of Communication, Resources, Disposition and Bureaucratic Structure. The inhibiting factor is the limited number of people who are skilled in providing services. Some employees are not skilled in carrying out their duties, resulting in a backlog of work, which is an obstacle in serving the White Water Crossing technical service unit.